Diversity of Ground-Dwelling Ants (Hymenoptera: Formicidae) in Phulchowki Hill, Lalitpur, Nepal - Adhikari, Tulsi Raj; Shakya, Shubha Ratna; Adhikari, Shambhu; Subedi, Indra Prasad (Tribhuvan University Journal, 2020)
The study assesses the diversity of ground-dwelling ants (Hymenoptera: Formicidae) in Phulchowki Hill, Lalitpur, Nepal focusing their species richness altitudinally and seasonally. Ants were sampled from June 2018 to February 2019using pitfall traps, bait traps and hand collection methods covering an altitudinal range from 1500 m to 2700 m in five selected sites (1500 m, 1800 m, 2100 m,2400 m, and 2700 m). A total of 1443 specimens representing four subfamilies, 12genera and 18 morph species were collected. Formicinae (57.58%) was recorded as the most abundant subfamily followed by Myrmicinae (38.53%), Ponerinae (2.21%) and Pseudomyrmicinae (1.66%). Camponotus was the most speciose (4morphospecies) genus and was most abundant in all seasons. The highest Similarity index (0.667) was recorded between the first and second sites among five sites. Species richness (16), Shannon diversity index (1.504) and abundance (631) were the highest in autumn. Similarly, species richness (12), Shannon diversity index (1.399) and species evenness (0.563) were recorded highest at 2100 m altitude, while species abundance (519) was maximum at 1500 m.